Golden bananas in the field: elevated fruit pro‐vitamin A from the expression of a single banana transgene. Issue 4 (20th December 2016) - Paul, Jean‐Yves; Khanna, Harjeet; Kleidon, Jennifer; Hoang, Phuong; Geijskes, Jason; Daniells, Jeff; Zaplin, Ella; Rosenberg, Yvonne; James, Anthony; Mlalazi, Bulukani; Deo, Pradeep; Arinaitwe, Geofrey; et al.
Summary: Vitamin A deficiency remains one of the world's major public health problems despite food fortification and supplements strategies. Biofortification of staple crops with enhanced levels of pro‐vitamin A (PVA) offers a sustainable alternative strategy to both food fortification and supplementation. As a proof of concept, PVA‐biofortified transgenic Cavendish bananas were generated and field trialed in Australia with the aim of achieving a target level of 20 μg/g of dry weight (dw) β‐carotene equivalent (β‐CE) in the fruit. Expression of a Fe'i banana‐derived phytoene synthase 2a ( MtPsy2a ) gene resulted in the generation of lines with PVA levels exceeding the target level with one line reaching 55 μg/g dw β‐CE. Expression of the maize phytoene synthase 1 ( ZmPsy1 ) gene, used to develop 'Golden Rice 2', also resulted in increased fruit PVA levels although many lines displayed undesirable phenotypes. Constitutive expression of either transgene with the maize polyubiquitin promoter increased PVA accumulation from the earliest stage of fruit development. In contrast, PVA accumulation was restricted to the late stages of fruit development when either the banana 1‐aminocyclopropane‐1‐carboxylate oxidase or the expansin 1 promoters were used to drive the same transgenes. Wild‐type plants with the longest fruit development time had also the highest fruit PVA concentrations. The results from this study suggest that early activation of the rate‐limiting enzyme in the carotenoid biosynthetic pathway and extended fruit maturation time are essential factors to achieve optimal PVA concentrations in banana fruit.